Tops & bottoms - Stevens, Janet (San Diego : Harcourt Brace, 1995)
Hare turns his bad luck around by striking a clever deal with the rich and lazy bear down the road.
Keywords: African Americans -- Folklore; Hares -- Folklore; Bears -- Folklore; Folklore -- United States